Qatar population-specific centile charts of placental weight in 80 722 newborns: relation to maternal age, gestational age, newborn birth weight, and gender, between the 37 th and 42 nd weeks of gestation: Placental weight centiles and factors affecting it - Alyafei, Fawzia; Soliman, Ashraf T; De Sanctis , Vincenzo; Al-Qubasi, Mai; Olukade , Tawa; Alaaraj, Nada; Hamed , Noor; Ahmed, Shayma; Soliman, Nada; Yassin , Doaa (Acta Biomedica Atenei Parmensis, 2023)
Background: Data about placental weight (PW) in relation to birth weight (BW) and gestational age (GA) are lacking in Arabic countries. Aims of the study: (a) to find out the national PW standards for babies born between 37th and 42nd weeks of gestation in male and female babies born in Qatar; (b) to study the relation, if any, between PW and maternal age, gestational age (GA), birth weight (BW), and gender of the newborn. Materials and Methods: A National population-based retrospective chart review study was conducted between 1-2016 to 12-2019 (n = 80 722). Data of gestational age (GA) at delivery (in weeks), newborn birth weight (BW), PW, and gender at birth, were collected from singleton babies born between 37 th and 42nd weeks of gestation. Results: The PW ranged from 440 to 860 grams (g) with a mean of 682 ± 96 g. at term for boys and 673 ± 94 g. for girls. The mean BW was 3 036 ± 448 g and BW/PW ratio was 0.203 ± 0.026. The PW continued to increase through 41 weeks’ gestation, in boys and girls with a significant decrease at the 42nd week of gestation. PW was significantly correlated with BW (r = 0.596, P: < 0.001) and GA (r = 0.15, P: <0.001) and accounted for 43.4% of the explained variability in birth weight. Conclusions: PW was a significant predictor of BW with a consistent increase in PW until the 41st week of gestation in boys and girls and a positive correlation with BW and GA.